Upaya Meningkatkan Motivasi Dan Hasil Belajar Matematika Melalui Model Pembelajaran Tipe Think Pair Square - Danti Andriani; Esti Harini (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
The purpose of this research was to increase being motivation and result in learning mathematics throughlearning modelStudent Teams Achievement Division of students class VIIID SMP Negeri 2 Pleret. The type of this research was a Classroom Action Research(CAR), accumulate data by questionnaire technique, test and documentation. The subject of this research were the students class VIII D SMP Negeri 3 Pleret in years 2017/ 2018. It consists of 28 students. The object of this research were students’ being motivation and result in learning mathematics through cooperative learning model type Think Pair Square. The result of the study shows that after applying this learning model, students’ being motivation and result has an increase. Students’ being motivation has an increase in pre cycle  from 69,78% become 74,28% in cycle I and increase 78,80% in cycle IIby the observation sheet. Beside that, the subjection mean of student learning result has an increase. In pre-action shows 59,5 with Minumum Completeness Criteria is 28,57% consist of 8 students, in cycle I has an increase become 72,96 with Minumum Completeness Criteria is 53,57% consist of 15 students, whereas in cycle II shows the increse become 83,26 with Minumum Completeness Criteria is 78,57% consist of 22 students.